A lithium ion battery positive electrode material and its preparation method and application
Ni-Co-Mn precursor was prepared by co-precipitation method and surface modified and coated. Combined with alumina and magnesium oxide doping, the poor circulation performance and safety hazards of high-nickel ternary cathode materials were solved, and the stability and performance of the material were improved.
Patent Information
- Application Number
- CN202411954755.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The high-nickel ternary cathode material has problems such as many residual alkalis on the surface, easy to react side effects with the electrolyte, poor circulation performance and safety hazards, and the existing coating methods have problems such as poor uniformity and insufficient reliability.
Ni-Co-Mn precursor was prepared by co-precipitation method, the surface was coated with SiO2 layer, and modified by tannin acid and coupled with UiO-66-NH2, doped with alumina and magnesium oxide, added with lithium salt and ball milling and calcining to prepare the cathode material of lithium-ion battery.
The stability of the material is improved, the cationic mixed discharge is reduced, the capacity retention rate is improved after multiple cycles, the circulation stability and rate performance of the material is improved, and the initial discharge capacity and Coulomb efficiency are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a positive electrode material for a lithium ion battery and a preparation method and application thereof. Background Art
[0002] As a new type of green power source, lithium-ion batteries have the advantages of high specific energy, green safety and environmental protection, and are therefore considered as a transmission medium for new energy and are widely used in electric vehicles, power tools, energy storage power stations and other fields. The four key materials of lithium-ion batteries are positive electrode materials, negative electrode materials, diaphragms and electrolytes, and their properties affect the final performance of lithium-ion batteries.
[0003] The cathode material is the most critical material for lithium-ion batteries, which determines the battery operating voltage, life, capacity, safety and cost, and its cost accounts for about 30-40% of the manufacturing cost of lithium-ion batteries. At present, the cathode materials of lithium batteries mainly include ternary materials (NCM, NCA), lithium iron phosphate (LFP), lithium cobalt oxide (LCO) and lithium manganese oxide (LMO) materials.
[0004] Among them, nickel cobalt manganese oxide ternary material (NCM material) as a lithium-ion battery positive electrode material has the characteristics of high specific capacity and high energy density compared to lithium iron phosphate, and has become the focus of the current positive electrode material research field. With the increase of nickel content, the specific capacity and energy density of nickel cobalt manganese oxide ternary material also increase. Therefore, high nickel ternary positive electrode materials represented by 811 and NCA have attracted much attention.
[0005] Although high-nickel ternary positive electrode materials have many advantages, they still have some shortcomings: for example, the residual alkali (mainly LiOH and Li2CO3) content on the surface of high-nickel ternary positive electrode materials is relatively high, which affects the processing performance of the electrode slurry and even causes the prepared battery cells to produce flatulence and bulging during the cycle. In addition, high-nickel ternary positive electrode materials are prone to reverse reactions with the electrolyte when fully charged, resulting in a decrease in the capacity of the battery cell, deterioration of the cycle performance, and even safety hazards. Generally, coating is the most common surface modification method for high-nickel ternary positive electrode materials, which can not only protect the positive electrode material and improve the stability in the electrolyte, but can even reduce the residual alkali on the surface and improve the lithium ion conductivity and electronic conductivity. However, the existing coating mainly adopts metal oxides such as aluminum oxide and zirconium oxide to mechanically mix and then perform high-temperature sintering coating. Metal oxides are mostly semiconductors or insulators. While they provide protection, they also hinder the conduction of lithium ions and electrons. In addition, it is difficult to achieve uniform coating by mechanical mixing. The coating layer obtained by high-temperature sintering is not firm. During the charge and discharge cycle, it will fall off with the insertion and removal of lithium ions, increasing the impedance of the battery. Therefore, this coating has technical problems such as sacrificing some performance, difficulty in uniform coating and unreliable coating. Summary of the invention
[0006] The purpose of the present invention is to provide a lithium ion battery positive electrode material and a preparation method and application thereof, which improves the stability of the material, reduces cation mixing, improves the capacity retention rate after multiple cycles, improves the cycle stability and rate performance of the material, improves the initial discharge capacity and coulomb efficiency, and has broad application prospects.
[0007] The technical solution of the present invention is achieved in this way:
[0008] The present invention provides a method for preparing a positive electrode material for a lithium ion battery. A Ni-Co-Mn precursor is prepared by a coprecipitation method, a SiO2 layer is coated on the surface, tannic acid is modified, coupled with UiO-66-NH2, mixed with aluminum oxide and magnesium oxide, lithium salt is added, ball milling is performed, and calcination is performed to obtain a positive electrode material for a lithium ion battery. The method specifically comprises the following steps:
[0009] S1. Preparation of a precursor: dissolving a nickel salt, a cobalt salt and a manganese salt in water, adding ascorbic acid, heating and stirring, adding aqueous ammonia to adjust the pH value of the solution, filtering, washing and drying to obtain a precursor;
[0010] S2. Preparation of SiO2 / precursor: dissolving alkyl orthosilicate in ethanol, adding the precursor, stirring and mixing, dropping ammonia water, heating and stirring to react, centrifuging, washing, drying, and calcining to obtain SiO2 / precursor;
[0011] S3. Tannic acid modification: SiO2 / precursor is added to water, tannic acid and a catalyst are added, heated and stirred for reaction, centrifuged, washed, and dried to obtain a modified SiO2 / precursor;
[0012] S4. Preparation of UiO-66-NH2: Add benzoic acid and ZrCl4 to DMF, add 2-aminoterephthalic acid, mix evenly by ultrasonication, hydrothermally react, centrifuge, wash, dry, ball mill, add to methanol and reflux, centrifuge, dry, and obtain UiO-66-NH2;
[0013] S5. Coupling: adding the modified SiO2 / precursor to water, adding NHS and EDC, stirring for activation, adding UiO-66-NH2, stirring for reaction, centrifuging, washing, and drying to obtain UiO-66-NH2 / modified SiO2 / precursor;
[0014] S6. Al / Mg doping: Alumina, magnesium oxide and UiO-66-NH2 / modified SiO2 / precursor are mixed evenly, lithium salt is added, ball milled, and calcined to obtain a positive electrode material for a lithium-ion battery.
[0015] As a further improvement of the present invention, the molar ratio of the nickel salt, cobalt salt, manganese salt and ascorbic acid in step S1 is 7-9.5:0.2-1.5:0.3-2:15-20, the heating and stirring temperature is 45-55°C, the time is 20-30min, the pH value of the solution is adjusted to 10-11 by dripping ammonia water, the nickel salt is nickel nitrate or nickel sulfate, the cobalt salt is cobalt sulfate or cobalt nitrate, and the manganese salt is manganese nitrate or manganese sulfate.
[0016] As a further improvement of the present invention, the alkyl orthosilicate in step S2 is methyl orthosilicate or ethyl orthosilicate, the mass ratio of the alkyl orthosilicate, the precursor and ammonia water is 3-5:10:1-2, the temperature of the heating and stirring reaction is 45-55°C, the time is 7-10h, and the calcination temperature is 400-500°C, and the time is 1-3h.
[0017] As a further improvement of the present invention, the mass ratio of SiO2 / precursor, tannic acid and catalyst in step S3 is 10:2-4:0.2-0.3, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 50-60°C, and the time is 2-4h.
[0018] As a further improvement of the present invention, the mass ratio of benzoic acid, ZrCl4 and 2-aminoterephthalic acid in step S4 is 3-5:0.7-0.9:0.4-0.8, the temperature of the hydrothermal reaction is 120-130°C, the time is 18-20h, and the reflux time is 5-7h.
[0019] As a further improvement of the present invention, the mass ratio of modified SiO2 / precursor, NHS, EDC, and UiO-66-NH2 in step S5 is 10:1-2:1-2:3-5, and the stirring reaction time is 10-12h.
[0020] As a further improvement of the present invention, the mass ratio of aluminum oxide, magnesium oxide, UiO-66-NH2 / modified SiO2 / precursor in step S6 is 0.1-0.2:0.05-0.1:10, the amount of lithium salt added is calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1-1.1:1, the calcination temperature is 700-900°C, the time is 5-20h, and the lithium salt is lithium hydroxide.
[0021] The present invention further protects a lithium ion battery positive electrode material prepared by the above preparation method.
[0022] The present invention further protects the use of the above-mentioned lithium-ion battery positive electrode material in the preparation of lithium-ion batteries for new energy vehicles, energy storage systems, and aviation fields.
[0023] The present invention has the following beneficial effects:
[0024] Nickel-cobalt-manganese ternary lithium-ion positive electrode materials combine the advantages of three layered materials, LiCoO2, LiMnO2, and LiNiO2, and have the characteristics of high available capacity and high energy density. However, NCM still has the inherent defects of LiNiO2, LiCoO2, and LiMnO2. During use, there are problems such as low Coulomb efficiency, capacity attenuation, high temperature adaptability, and poor safety caused by element mixing, phase change, poor thermal stability, and microcracks, which hinder its widespread application. Researchers often use modification to improve performance. In NCM materials, Co has a valence of +3, Mn has a valence of +4, and Ni is the main electrochemically active substance with a valence of +2 and +3. Its content determines the capacity of the material, and increasing its content can increase the capacity. However, Ni will produce Ni during the cycle. 2+ , Ni 2+ With Li + When the radius is close, Li-Ni mixing will occur, resulting in a decrease in cycle performance.
[0025] After the Co-Mn-Ni precursor is prepared, silicon dioxide is deposited on the surface through a sol-gel reaction. During the charge and discharge process, the presence of the coating layer effectively stabilizes the material structure, inhibits the occurrence of side reactions, and improves the cycle performance and rate performance. The surface is further modified by tannic acid, and the tannic acid layer with carbonyl functional groups effectively alleviates the occurrence of surface side reactions, improves the initial discharge capacity and coulomb efficiency, and can also couple with UiO-66-NH2 through carboxyl groups so that UiO-66-NH2 can be deposited and coated on the surface of the precursor material. Compared with direct mechanical mixing of zirconia materials, the coupling method of the present invention has better dispersibility, a larger specific surface area of the metal organic framework structure, and provides more active sites and lithium storage sites, thereby improving the ion migration rate. At the same time, the organic ligand can be used as a carbon source to create a uniform nanocarbon matrix or a three-dimensional carbon framework for the electrode material, thereby enhancing the electronic conductivity of the positive electrode material. During the subsequent calcination process of the Zr metal organic framework coating, part of the Zr ions penetrate from the coating layer into the NCM interior, and the synergistic effect of ion doping and coating improves the capacity retention rate of the NCM after multiple cycles, and its modification effect is also better than the method of mechanically mixing zirconia.
[0026] The mixing of Al and Mg has an ion radius larger than that of nickel ions, which increases the c / a value of NCM and makes it easy to form an ordered layered structure. After multiple cycles, there is still a high capacity retention rate, which improves the cycle stability of the material. The mixing of the two has a synergistic effect. At the same time, the zirconium ions, magnesium ions, and aluminum ions doped in the outer layer will occupy the nickel and lithium sites at the same time, forming a fast ion conductor on the surface, improving the stability of the crystal structure, playing a supporting role in the process of lithium extraction / insertion, and reducing cation mixing.
[0027] The lithium ion battery positive electrode material prepared by the invention improves the stability of the material, reduces cation mixing, improves the capacity retention rate after multiple cycles, improves the cycle stability and rate performance of the material, improves the initial discharge capacity and coulomb efficiency, and has broad application prospects. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] NHS, N-hydroxysuccinimide, EDC, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, DMF, N,N-dimethylformamide.
[0030] Example 1
[0031] This embodiment provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:
[0032] S1. Preparation of the precursor: 85 mmol nickel sulfate, 10 mmol cobalt sulfate, and 5 mmol manganese sulfate were dissolved in 100 mL water, 150 mmol ascorbic acid was added, heated to 45 ° C, stirred for 20 min, ammonia was added dropwise to adjust the pH value of the solution to 10, filtered, washed, and dried to obtain a precursor;
[0033] S2. Preparation of SiO2 / precursor: 3 g of methyl orthosilicate was dissolved in 50 mL of ethanol, 10 g of the precursor was added, the mixture was stirred for 10 min, 1 g of ammonia water was added dropwise, the mixture was heated to 45°C, stirred for 7 h, centrifuged, washed, dried, and calcined at 400°C for 1 h to obtain SiO2 / precursor;
[0034] S3. Tannic acid modification: 10 g SiO2 / precursor was added to 100 mL water, 2 g tannic acid and 0.2 g catalyst were added, heated to 50°C, stirred for 2 h, centrifuged, washed, and dried to obtain modified SiO2 / precursor;
[0035] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0036] S4. Preparation of UiO-66-NH2: 3 g benzoic acid and 0.7 g ZrCl4 were added to 200 mL DMF, and 0.4 g 2-aminoterephthalic acid was added. The mixture was ultrasonically mixed at 1000 W for 15 min, and hydrothermally reacted at 120 ° C for 18 h. The mixture was centrifuged, washed, dried, and ball-milled for 1 h. The mixture was added to methanol and heated under reflux for 5 h. The mixture was centrifuged and dried to obtain UiO-66-NH2.
[0037] S5. Coupling: 10 g of modified SiO2 / precursor was added to 200 mL of water, 1 g of NHS and 1 g of EDC were added, and the mixture was stirred for activation for 30 min, 3 g of UiO-66-NH2 was added, and the reaction was stirred for 10 h, centrifuged, washed, and dried to obtain UiO-66-NH2 / modified SiO2 / precursor;
[0038] S6. Al / Mg doping: 0.1 g aluminum oxide, 0.05 g magnesium oxide and 10 g UiO-66-NH2 / modified SiO2 / precursor were stirred and mixed for 15 min, lithium hydroxide was added, and the amount of lithium hydroxide added was calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1:1. The mixture was ball milled for 1 h and calcined at 700°C for 5 h to obtain a lithium-ion battery positive electrode material.
[0039] Example 2
[0040] This embodiment provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:
[0041] S1. Preparation of precursor: 85mmol nickel sulfate, 10mmol cobalt sulfate, 5mmol manganese sulfate were dissolved in 100mL water, 200mmol ascorbic acid was added, heated to 55°C, stirred for 30min, ammonia was added dropwise to adjust the pH value of the solution to 11, filtered, washed, and dried to obtain a precursor;
[0042] S2. Preparation of SiO2 / precursor: 5 g of tetraethyl orthosilicate was dissolved in 50 mL of ethanol, 10 g of the precursor was added, the mixture was stirred for 10 min, 2 g of ammonia water was added dropwise, the mixture was heated to 55°C, stirred for 10 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to obtain SiO2 / precursor;
[0043] S3. Tannic acid modification: 10 g SiO2 / precursor was added to 100 mL water, 4 g tannic acid and 0.3 g catalyst were added, heated to 60°C, stirred for 4 h, centrifuged, washed, and dried to obtain a modified SiO2 / precursor;
[0044] The catalyst is a Tris-HCl solution with a pH of 9.5;
[0045] S4. Preparation of UiO-66-NH2: 5 g benzoic acid and 0.9 g ZrCl4 were added to 200 mL DMF, and 0.8 g 2-aminoterephthalic acid was added, and ultrasonic mixing was performed at 1000 W for 15 min, and hydrothermal reaction was performed at 130 ° C for 20 h, centrifuged, washed, dried, ball milled for 1 h, added to methanol, heated under reflux for 7 h, centrifuged, and dried to obtain UiO-66-NH2;
[0046] S5. Coupling: 10 g of modified SiO2 / precursor was added to 200 mL of water, 2 g of NHS and 2 g of EDC were added, and the mixture was stirred for activation for 30 min, 5 g of UiO-66-NH2 was added, and the reaction was stirred for 12 h, centrifuged, washed, and dried to obtain UiO-66-NH2 / modified SiO2 / precursor;
[0047] S6. Al / Mg doping: 0.2 g aluminum oxide, 0.1 g magnesium oxide and 10 g UiO-66-NH2 / modified SiO2 / precursor were stirred and mixed for 15 min, lithium hydroxide was added, and the amount of lithium hydroxide added was calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1.1:1, ball milled for 1 h, and calcined at 900°C for 20 h to obtain a lithium-ion battery positive electrode material.
[0048] Example 3
[0049] This embodiment provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:
[0050] S1. Preparation of the precursor: 85 mmol nickel sulfate, 10 mmol cobalt sulfate, and 5 mmol manganese sulfate were dissolved in 100 mL water, 170 mmol ascorbic acid was added, heated to 50 ° C, stirred for 25 min, ammonia was added dropwise to adjust the pH value of the solution to 10.5, filtered, washed, and dried to obtain a precursor;
[0051] S2. Preparation of SiO2 / precursor: 4 g of tetraethyl orthosilicate was dissolved in 50 mL of ethanol, 10 g of the precursor was added, the mixture was stirred for 10 min, 1.5 g of ammonia water was added dropwise, the mixture was heated to 50°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 450°C for 2 h to obtain SiO2 / precursor;
[0052] S3. Tannic acid modification: 10 g SiO2 / precursor was added to 100 mL water, 3 g tannic acid and 0.25 g catalyst were added, heated to 55°C, stirred for 3 h, centrifuged, washed, and dried to obtain a modified SiO2 / precursor;
[0053] The catalyst is a Tris-HCl solution with a pH of 9;
[0054] S4. Preparation of UiO-66-NH2: 4 g benzoic acid and 0.8 g ZrCl4 were added to 200 mL DMF, and 0.6 g 2-aminoterephthalic acid was added. The mixture was ultrasonically mixed at 1000 W for 15 min, and hydrothermally reacted at 125 °C for 19 h. The mixture was centrifuged, washed, dried, and ball-milled for 1 h. The mixture was added to methanol and heated under reflux for 6 h. The mixture was centrifuged and dried to obtain UiO-66-NH2.
[0055] S5. Coupling: 10 g of modified SiO2 / precursor was added to 200 mL of water, 1.5 g of NHS and 1.5 g of EDC were added, and the mixture was stirred for activation for 30 min. 4 g of UiO-66-NH2 was added, and the mixture was stirred for reaction for 11 h. The mixture was centrifuged, washed, and dried to obtain UiO-66-NH2 / modified SiO2 / precursor.
[0056] S6. Al / Mg doping: 0.15 g aluminum oxide, 0.07 g magnesium oxide and 10 g UiO-66-NH2 / modified SiO2 / precursor were stirred and mixed for 15 min, lithium hydroxide was added, and the amount of lithium hydroxide added was calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1.05:1. The mixture was ball milled for 1 h and calcined at 800°C for 10 h to obtain a lithium-ion battery positive electrode material.
[0057] Comparative Example 1
[0058] Compared with Example 3, the difference is that step S2 is not performed.
[0059] The details are as follows:
[0060] S1. Preparation of the precursor: 85 mmol nickel sulfate, 10 mmol cobalt sulfate, and 5 mmol manganese sulfate were dissolved in 100 mL water, 170 mmol ascorbic acid was added, heated to 50 ° C, stirred for 25 min, ammonia was added dropwise to adjust the pH value of the solution to 10.5, filtered, washed, and dried to obtain a precursor;
[0061] S2. Tannic acid modification: 10 g of the precursor was added to 100 mL of water, 3 g of tannic acid and 0.25 g of a catalyst were added, heated to 55°C, stirred for 3 h, centrifuged, washed, and dried to obtain a modified precursor;
[0062] The catalyst is a Tris-HCl solution with a pH of 9;
[0063] S3. Preparation of UiO-66-NH2: 4 g benzoic acid and 0.8 g ZrCl4 were added to 200 mL DMF, and 0.6 g 2-aminoterephthalic acid was added. The mixture was ultrasonically mixed at 1000 W for 15 min, and hydrothermally reacted at 125 °C for 19 h. The mixture was centrifuged, washed, dried, and ball-milled for 1 h. The mixture was added to methanol and heated under reflux for 6 h. The mixture was centrifuged and dried to obtain UiO-66-NH2.
[0064] S4. Coupling: 10 g of the modified precursor was added to 200 mL of water, 1.5 g of NHS and 1.5 g of EDC were added, and the mixture was stirred for activation for 30 min, 4 g of UiO-66-NH2 was added, and the mixture was stirred for reaction for 11 h, centrifuged, washed, and dried to obtain UiO-66-NH2 / modified precursor;
[0065] S5. Al / Mg doping: 0.15 g aluminum oxide, 0.07 g magnesium oxide and 10 g UiO-66-NH2 / modified precursor were stirred and mixed for 15 min, lithium hydroxide was added, and the amount of lithium hydroxide added was calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1.05:1. The mixture was ball milled for 1 h and calcined at 800°C for 10 h to obtain a lithium-ion battery positive electrode material.
[0066] Comparative Example 2
[0067] Compared with Example 3, the difference is that step S3 is not performed.
[0068] The details are as follows:
[0069] S1. Preparation of the precursor: 85 mmol nickel sulfate, 10 mmol cobalt sulfate, and 5 mmol manganese sulfate were dissolved in 100 mL water, 170 mmol ascorbic acid was added, heated to 50 ° C, stirred for 25 min, ammonia was added dropwise to adjust the pH value of the solution to 10.5, filtered, washed, and dried to obtain a precursor;
[0070] S2. Preparation of SiO2 / precursor: 4 g of tetraethyl orthosilicate was dissolved in 50 mL of ethanol, 10 g of the precursor was added, the mixture was stirred for 10 min, 1.5 g of ammonia water was added dropwise, the mixture was heated to 50°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 450°C for 2 h to obtain SiO2 / precursor;
[0071] S3. Preparation of UiO-66-NH2: 4 g benzoic acid and 0.8 g ZrCl4 were added to 200 mL DMF, and 0.6 g 2-aminoterephthalic acid was added. The mixture was ultrasonically mixed at 1000 W for 15 min, and hydrothermally reacted at 125 °C for 19 h. The mixture was centrifuged, washed, dried, and ball-milled for 1 h. The mixture was added to methanol and heated under reflux for 6 h. The mixture was centrifuged and dried to obtain UiO-66-NH2.
[0072] S4 mixing: 10g SiO2 / precursor was added to 200mL water, 4g UiO-66-NH2 was added, stirred and mixed for 30min, centrifuged, washed, and dried to obtain a UiO-66-NH2 / SiO2 / precursor mixture;
[0073] S5. Al / Mg doping: 0.15 g aluminum oxide, 0.07 g magnesium oxide and 10 g UiO-66-NH2 / SiO2 / precursor mixture were stirred and mixed for 15 min, lithium hydroxide was added, and the amount of lithium hydroxide added was calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1.05:1, ball milled for 1 h, and calcined at 800°C for 10 h to obtain a lithium-ion battery positive electrode material.
[0074] Comparative Example 3
[0075] Compared with Example 3, the difference is that steps S3, S4 and S5 are not performed.
[0076] The details are as follows:
[0077] S1. Preparation of the precursor: 85 mmol nickel sulfate, 10 mmol cobalt sulfate, and 5 mmol manganese sulfate were dissolved in 100 mL water, 170 mmol ascorbic acid was added, heated to 50 ° C, stirred for 25 min, ammonia was added dropwise to adjust the pH value of the solution to 10.5, filtered, washed, and dried to obtain a precursor;
[0078] S2. Preparation of SiO2 / precursor: 4 g of tetraethyl orthosilicate was dissolved in 50 mL of ethanol, 10 g of the precursor was added, the mixture was stirred for 10 min, 1.5 g of ammonia water was added dropwise, the mixture was heated to 50°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 450°C for 2 h to obtain SiO2 / precursor;
[0079] S3. Al / Mg doping: 0.15 g aluminum oxide, 0.07 g magnesium oxide and 10 g SiO2 / precursor were stirred and mixed for 15 min, lithium hydroxide was added, and the amount of lithium hydroxide added was calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1.05:1, ball milled for 1 h, and calcined at 800°C for 10 h to obtain a lithium-ion battery positive electrode material.
[0080] Comparative Example 4
[0081] Compared with Example 3, the difference is that no aluminum oxide is added in step S6.
[0082] The details are as follows:
[0083] S6. Mg doping: 0.22 g of magnesium oxide and 10 g of UiO-66-NH2 / modified SiO2 / precursor were stirred and mixed for 15 min, and lithium hydroxide was added. The amount of lithium hydroxide added was calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1.05:1. The mixture was ball milled for 1 h and calcined at 800°C for 10 h to obtain a lithium-ion battery positive electrode material.
[0084] Comparative Example 5
[0085] Compared with Example 3, the difference is that magnesium oxide is not added in step S6.
[0086] The details are as follows:
[0087] S6. Al doping: 0.22 g of aluminum oxide and 10 g of UiO-66-NH2 / modified SiO2 / precursor were stirred and mixed for 15 min, and lithium hydroxide was added. The amount of lithium hydroxide added was calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1.05:1. The mixture was ball milled for 1 h and calcined at 800°C for 10 h to obtain a lithium-ion battery positive electrode material.
[0088] Comparative Example 6
[0089] Compared with Example 3, the difference is that aluminum oxide and magnesium oxide are not added in step S6.
[0090] The details are as follows:
[0091] S6. Preparation of positive electrode materials for lithium-ion batteries: 10 g of UiO-66-NH2 / modified SiO2 / precursor was stirred and mixed for 15 min, lithium hydroxide was added, and the amount of lithium hydroxide added was calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1.05:1, ball milled for 1 h, and calcined at 800°C for 10 h to obtain a positive electrode material for lithium-ion batteries.
[0092] Test Example 1
[0093] The positive electrode material of lithium ion battery prepared in Example 1-3 or Comparative Example 1-6 was mixed with conductive agent SP and binder polyvinylidene fluoride in a mass ratio of 8:1:1, and N-methylpyrrolidone was used as solvent, and then coated on carbon-coated aluminum foil, dried at 105°C for 6 hours, and compacted on a roller press to prepare a positive electrode sheet. A metal lithium sheet was used as a negative electrode sheet, a 1 mol / L LiPF6 solution was used as an electrolyte, and Cellgard 2300 was used as a diaphragm, and assembled into a button cell with the above positive electrode sheet. The battery performance was tested, and the results are shown in Table 1.
[0094] Table 1
[0095]
[0096] It can be seen from the above table that the batteries made from the lithium ion battery positive electrode materials prepared in Examples 1-3 of the present invention have better electrical performance.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material for a lithium ion battery, characterized in that: The Ni-Co-Mn precursor is prepared by coprecipitation, the surface is coated with SiO2 layer, tannic acid is modified, coupled with UiO-66-NH2, mixed with alumina and magnesium oxide, lithium salt is added, ball milled, calcined, and the positive electrode material of lithium ion battery is obtained, which specifically includes the following steps: S1. Preparation of a precursor: dissolving a nickel salt, a cobalt salt and a manganese salt in water, adding ascorbic acid, heating and stirring, adding aqueous ammonia to adjust the pH value of the solution, filtering, washing and drying to obtain a precursor; S2. Preparation of SiO2 / precursor: dissolving alkyl orthosilicate in ethanol, adding the precursor, stirring and mixing, dropping ammonia water, heating and stirring to react, centrifuging, washing, drying, and calcining to obtain SiO2 / precursor; S3. Tannic acid modification: SiO2 / precursor is added to water, tannic acid and a catalyst are added, heated and stirred for reaction, centrifuged, washed, and dried to obtain a modified SiO2 / precursor; S4. Preparation of UiO-66-NH2: Add benzoic acid and ZrCl4 to DMF, add 2-aminoterephthalic acid, mix evenly by ultrasonication, hydrothermally react, centrifuge, wash, dry, ball mill, add to methanol and reflux, centrifuge, dry, and obtain UiO-66-NH2; S5. Coupling: adding the modified SiO2 / precursor to water, adding NHS and EDC, stirring for activation, adding UiO-66-NH2, stirring for reaction, centrifuging, washing, and drying to obtain UiO-66-NH2 / modified SiO2 / precursor; S6. Al / Mg doping: Al2O3, MgO and UiO-66-NH2 / modified SiO2 / precursor are mixed evenly, lithium salt is added, ball milled and calcined to obtain the positive electrode material of lithium-ion battery.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the nickel salt, cobalt salt, manganese salt and ascorbic acid in step S1 is (7-9.5): (0.2-1.5): (0.3-2): (15-20), the heating and stirring temperature is 45-55°C, the time is 20-30min, the pH value of the solution is adjusted to 10-11 by dropping ammonia water, the nickel salt is nickel nitrate or nickel sulfate, the cobalt salt is cobalt sulfate or cobalt nitrate, and the manganese salt is manganese nitrate or manganese sulfate.
3. The preparation method according to claim 1, characterized in that In step S2, the alkyl orthosilicate is methyl orthosilicate or ethyl orthosilicate, and the mass ratio of the alkyl orthosilicate, precursor, and ammonia water is (3-5):10:(1-2). The temperature of the heating and stirring reaction is 45-55°C, the time is 7-10h, and the temperature of the calcination is 400-500°C, and the time is 1-3h.
4. The preparation method according to claim 1, characterized in that: The mass ratio of SiO2 / precursor, tannic acid and catalyst in step S3 is 10:(2-4):(0.2-0.3), the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 50-60°C, and the time is 2-4h.
5. The preparation method according to claim 1, characterized in that: The mass ratio of benzoic acid, ZrCl4 and 2-aminoterephthalic acid in step S4 is (3-5): (0.7-0.9): (0.4-0.8), the temperature of the hydrothermal reaction is 120-130°C, the time is 18-20h, and the reflux time is 5-7h.
6. The preparation method according to claim 1, characterized in that: The mass ratio of modified SiO2 / precursor, NHS, EDC, and UiO-66-NH2 in step S5 is 10:(1-2):(1-2):(3-5), and the stirring reaction time is 10-12 hours.
7. The preparation method according to claim 1, characterized in that: The mass ratio of aluminum oxide, magnesium oxide, UiO-66-NH2 / modified SiO2 / precursor in step S6 is (0.1-0.2): (0.05-0.1): 10, the amount of lithium salt added is calculated according to the molar ratio of Li / (Ni+Co+Mn) = 1-1.1: 1, the calcination temperature is 700-900°C, the time is 5-20h, and the lithium salt is lithium hydroxide.
8. A lithium ion battery positive electrode material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the lithium-ion battery positive electrode material as claimed in claim 8 in preparing lithium-ion batteries for new energy vehicles, energy storage systems, and aviation fields.
Citation Information
Patent Citations
High-energy density nickel-series composite positive electrode material for lithium ion battery and preparation method of high-energy density nickel-series composite positive electrode material
CN104124449A
Nano single crystal ternary material and preparation method thereof
CN114388747A